European Union and diaspora engagement policy within changing realities - Violina Mardari (CES Working Papers, 2017)
The article presents an analysis of the European Union and diaspora engagement policy within changing realities. The author focuses on the main research question concerning how the new, uncontrolled migration flows may influence the approach on diaspora engagement policy within member states. This process could have positive as well as negative implications for the Community space even if the EU attempts to develop a new legal framework on migration. The interdisciplinary approach and methods as empirical analysis, comparison and observation on some good practices and new issues gave the possibility to estimate the results of how changing diaspora role perception reduces the gap between different migrants in the EU and improves the diaspora engagement dialogue on institutional and civil society level.
Keywords: 330; diaspora engagement; good practices; migration; changing realities